Contemporary European Crime Fiction
XIV, 295 p.
Keywords: This book represents the first extended consideration of contemporary crime fiction as a European phenomenon. Understanding crime fiction in its broadest sense, as a transmedia practice, and offering unique insights into this practice in specific European countries and as a genuinely transcontinental endeavour, this book argues that the distinctiveness of the form can be found in its related historical and political inquiries. It asks how the genre’s excavation of Europe’s history of violence and protest in the twentieth century is informed by contemporary political questions. It also considers how the genre’s progressive reimagining of new identities forged at the crossroads of ethnicity, gender, and sexuality is offset by its bleaker assessment of the corrosive effects of entrenched social inequalities, political corruption, and state violence. The result is a rich, vibrant collection that shows how crime fiction can help us better understand the complex relationship between Europe’spast, present, and future. Seven chapters are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Monica Dall’Asta is Professor of Film and Media Studies at the University of Bologna, Italy. She is one of the founding editors of the Women Film Pioneers Project, based at Columbia University, and served as Coordinator of the DETECt-Detecting Transcultural Identity in European Popular Crime Narratives project (2018–21). Jacques Migozzi is Professor of French Literature at the University of Limoges, France, where he leads the Groupe de recherches sur les Littératures Populaires et Cultures Médiatiques. He published a synthetical essay in 2005, Boulevards du Populaire, and has edited or co-edited 12 volumes or journal special issues. Federico Pagello teaches Film and Media Studies at the University of Chieti-Pescara, Italy. His research focuses on popular serial narratives and their transmedia and transmedia circulation. His most recent monograph is entitled Quentin Tarantino and Film Theory: Aesthetics and Dialectics in Late Postmodernity (Palgrave 2020). Andrew Pepper is Professor of English at Queen’s University Belfast, Northern Ireland. He is author of Unwilling Executioner: Crime Fiction and the State (2016) and co-editor of Globalization and the State in Contemporary Crime Fiction (2016) and The Routledge Companion to Crime Fiction (2020). .